PERSUASIVE TECHNIQUE OF COMMERCIAL ADVERTISEMENTS ON BILLBOARD IN MEDAN - Reza Saputra Rambe; Busmin Gurning (State University of Medan, 2017)
This study deals with Persuasive Technique of Commercial Advertisement on Billboard in Medan. This study is aimed at analyzing: (1) persuasive technique applied in the commercial advertisement on billboard in Medan, and (2) the reason of using the persuasive technique in the billboard commercial advertisement. It employs descriptive qualitative research method to conduct this study with. The data of this study are pictures and writings in 33 the commercial advertisements which were displayed at Jl. Gatot Subroto and Jl. Gadjah Mada, Medan. The data is analyzed by using the theories from Keraf (1991) about the persuasive techniques. There are seven techniques were applied in the billboard commercial advertisements, they are Rationalization (10 of 33 advertisements), Identification (13 of 33 advertisements), Suggestion (20 of 33 advertisements), Conformity (7 of 33 advertisements), Compensation (9 of 33 advertisements), Displacement (1 of 33 advertisements), and Projection (7 of 33 advertisements). One advertisement could use more than one persuasive techniques. Furthermore, the reason why the persuaders applied the persuasive techniques is to make their readers believed what they said and wanted to buy and consume the products.